Unemployment Insurance, Unemployment Duration, and Excess Supply of Labour - Maki, Dennis (Relations industrielles / Industrial Relations, 1976)
This paper examines the effect of the unemployment insurance scheme on the duration of unemployment spells in Canada in the period 1953-1973.